Effect of Lens Fragmentation Patterns on Phacoemulsification Parameters and Postoperative Inflammation in Femtosecond Laser-Assisted Cataract Surgery. (3rd October 2018) - Kaur, Manpreet; Titiyal, Jeewan S.; Surve, Abhidnya; Falera, Ruchita; Verma, Meena
ABSTRACT: Purpose : To evaluate intraoperative and postoperative outcomes with "chop" or "matrix" lens fragmentation patterns in femtosecond laser-assisted cataract surgery. Methods : Prospective comparative study of 66 eyes with grade III–IV nuclear sclerosis was conducted at an apex tertiary care ophthalmic center. Cases were randomly allocated to undergo femtosecond laser pretreatment using matrix pattern (group I; n  = 33) or chop pattern (group II; n  = 33) of lens fragmentation (LenSx laser platform), followed by phacoemulsification. The primary outcome measures were intraoperative phacoemulsification parameters and postoperative anterior chamber (AC) flare. Secondary outcome measures were intraoperative complications, postoperative central macular thickness, visual acuity, and endothelial cell counts. Follow-up was performed on postoperative day (POD) 1 and 30. Results : Phacoemulsification parameters including cumulative dissipated energy ( p  = 0.008), ultrasonic time ( p  = 0.001), aspiration time ( p  < 0.001), and total duration ( p  = 0.001) were significantly less in group I. The AC flare was 9.8 ± 4.6 in group I and 15.4 ± 6.0 in group II ( p  < 0.001) on POD 1, and the difference persisted at 1 month. A highly significant positive correlation was observed between the total duration of phacoemulsification and AC flare ( p  < 0.001). No case developed cystoid macular edema. The postoperative specular counts were significantly less in group II on POD 1 ( p  = 0.036) and POD 30 ( p  = 0.02). There was no difference in visual acuity between the two groups, and intraoperative complications were not observed in any case. Conclusion : A decrease in phacoemulsification time and energy is observed after femtosecond laser pretreatment with the matrix pattern of lens fragmentation as compared to the chop pattern. The endothelial cell loss and postoperative inflammation is significantly less with the matrix pattern, and the inflammation correlates with the duration of phacoemulsification.